Pengaruh Pengaruh Struktur Aset, Profitabilitas, dan Likuiditas Terhadap Struktur Modal Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Zihan; Rizki Filhayati Rambe (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of asset structure, profitability, liquidity, and firm size on capital structure partially in food and beverage companies listed on the Indonesia Stock Exchange during the 2019–2023 period. In addition, this study also aims to determine the role of firm size as a moderating variable in strengthening or weakening the effect of asset structure, profitability, and liquidity on capital structure. The population of this study consisted of 83 food and beverage companies listed on the Indonesia Stock Exchange during the observation period. The sampling technique used was purposive sampling based on certain criteria, resulting in 17 companies as the research sample. With a five-year observation period, the total data used in this study amounted to 85 observations. The data analysis technique used was Moderated Regression Analysis (MRA) to examine the direct relationship between variables and the moderating effect of firm size. The results show that asset structure has a significant effect on capital structure, indicating that the composition of company assets is an important factor in determining financing policies. Profitability has no significant effect on capital structure, meaning that the level of company profits is not a primary factor in determining capital structure. Liquidity has a significant effect on capital structure, indicating that a company’s ability to meet short-term obligations is related to its financing decisions. Furthermore, firm size is unable to moderate the effect of asset structure, profitability, and liquidity on capital structure in food and beverage companies listed on the Indonesia Stock Exchange during the 2019–2023 period.